Prevalence and risk factors for oral human papillomavirus infection in Mexican HIV-infected men - Yuria Ablanedo-Terrazas; Karla Romero-Mora; María Gómez-Palacio; Claudia Alvarado-de la Barrera; Matilde Ruiz-Cruz; Ramón Hernández-Juan; Gustavo Reyes-Terán (Instituto Nacional de Salud Pública, 2018)
Objective. To determine the prevalence and risk factors for oral high-risk human papillomavirus (HR-HPV) infection in human immunodeficiency virus (HIV)-infected men. Materials and methods. Consecutive male outpatients with HIV-infection were enrolled. Demographic and behavioral risk data were obtained. Anal swabs and oral rinses were tested for HR-HPV DNA. Oral, pharyngeal and video laryngoscopy examinations were performed for detection of lesions. Results. The prevalence of HR-HPV oral infection was 9.3% (subtypes other than HR HPV 16/18 predominated). The prevalence of anal HR-HPV infection was 75.7%. The risk factors for oral infection with HR-HPV were tonsillectomy (OR=13.12) and years from HIV diagnosis (OR=1.17). Conclusions. Tonsillectomy and years from HIV diagnosis were associated with oral HPV infection. No association was found between oral and anal HR-HPV infections. This is the first study reporting the prevalence and risk factors for oral HR-HPV infection in Mexican HIV-infected population.